2022
DOI: 10.1002/1878-0261.13213
|View full text |Cite
|
Sign up to set email alerts
|

KSR induces RAS‐independent MAPK pathway activation and modulates the efficacy of KRAS inhibitors

Abstract: The kinase suppressor of rat sarcoma (RAS) proteins (KSR1 and KSR2) have long been considered as scaffolding proteins required for optimal mitogen‐activated protein kinase (MAPK) pathway signalling. However, recent evidence suggests that they play a more complex role within this pathway. Here, we demonstrate that ectopic expression of KSR1 or KSR2 is sufficient to activate the MAPK pathway and to induce cell proliferation in the absence of RAS proteins. In contrast, the ectopic expression of KSR proteins is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…These results suggest that altered sotorasib metabolism could, at least partially, contribute to tumor resistance due to a further reduction of its therapeutic efficacy. Ectopic expression of 3 of the most consistently upregulated genes involved in xenobiotic metabolism, Gstm1 , Gstm3 , and Gstm5 , readily caused an increase in GST activity and resistance to sotorasib in PDX-dc1 and MIA Paca-2 human tumor cells known to be sensitive to sotorasib ( 30 ) ( Figure 7, E and F , and Supplemental Figure 10 ), indicating that the GSTM class of detoxifying enzymes can modify the response to sotorasib, resulting in its reduced antitumor activity.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that altered sotorasib metabolism could, at least partially, contribute to tumor resistance due to a further reduction of its therapeutic efficacy. Ectopic expression of 3 of the most consistently upregulated genes involved in xenobiotic metabolism, Gstm1 , Gstm3 , and Gstm5 , readily caused an increase in GST activity and resistance to sotorasib in PDX-dc1 and MIA Paca-2 human tumor cells known to be sensitive to sotorasib ( 30 ) ( Figure 7, E and F , and Supplemental Figure 10 ), indicating that the GSTM class of detoxifying enzymes can modify the response to sotorasib, resulting in its reduced antitumor activity.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that KSR2 is a scaffold protein that interacts with RAF and MEK to facilitate activation of ERK/MAPK module ( Roy et al, 2002 ). In addition, a recent study demonstrated that KSR1 and KSR2 when expressed at high levels can activate the MAPK pathway-independent of RAS ( Paniagua et al, 2022 ). Based on the published data that ERK effects on osteoblasts are mediated via mTOR signaling ( Kim et al, 2022 ), it is possible that KSR2 effects on bone are via MAPK-mediated regulation of mTOR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of resistance include acquisition of mutations in the binding pockets targeted by the drugs, secondary activating mutations in KRAS , pathogenic mutations in other members of the MAPK pathway, and oncogenic gene rearrangements/fusions and amplification of the KRAS G12C allele or the MET gene [ 50 , 51 ]. In particular, the activating mutation of the RAF can occur directly downstream of RAS [ 51 , 52 ].The upregulation of KRAS suppressor protein 1 (KSR1) has been identified as a mechanism for resistance to Sotorasib [ 53 ]. KSR1 was found to act as a scaffolding protein that can bypass KRAS and continue signaling despite inhibition of KRAS G12C [ 53 , 54 ].…”
Section: Kras G12c Inhibitor Resistancementioning
confidence: 99%